Influence of Radiation Dose to Reconstructed Breast Following Mastectomy on Complication in Breast Cancer Patients Undergoing Two-Stage Prosthetic Breast Reconstruction - Chang, Jee Suk; Song, Seung Yong; Oh, Joo Hyun; Lew, Dae Hyun; Roh, Tai Suk; Kim, Se Young; Keum, Ki Chang; Lee, Dong Won; Kim, Yong Bae (Frontiers in Oncology, 2019)
Purpose: This study investigated the association between radiation dose and complication rate in patients who underwent breast reconstruction to understand the role of radiation hypofractionated regimen, boost radiation therapy (RT), and RT techniques. Methods: We retrospectively evaluated 75 patients treated with post-mastectomy adjuvant RT for breast cancer in the setting of two-stage prosthetic breast reconstruction. Near maximum radiation dose (Dmax) in the 2 cc or 0.03 cc of reconstructed breast or overlying breast skin was obtained from dose-volume histograms. Results: Post-RT complications occurred in 22.7% of patients. Receiver operating characteristic analysis showed that all near Dmax parameters were able to predict complication risk, which retained statistical significance after adjusting other variables (odds ratio 1.12 per Gy, 95% confidence interval 1.02-1.23) with positive dose-response relationship. In multiple linear regression model (R2 = 0.92), conventional fractionation (β = 11.7) and 16 fractions in 2.66 Gy regimen (β = 3.9) were the major determinants of near Dmax compared with 15 fractions in 2.66 Gy regimen, followed by utilization of boost RT (β = 3.2). The effect of bolus and dose inhomogeneity seemed minor (P >.05). The location of hot spot was not close to the high density metal area of the expander, but close to the surrounding areas of partially deflated expander bag. Conclusions: This study is the first to demonstrate a dose-response relationship between risk of complications and near Dmax, where hypofractionated regimen or boost RT can play an important role. Rigorous RT-quality assurance program and modification of dose constraints could be considered as a critically important component for ongoing trials of hypofractionation. Based on our findings, we initiated a multi-center retrospective study (KROG 18-04) and a prospective study (NCT03523078) to validate our findings.